2021
DOI: 10.1002/asia.202001404
|View full text |Cite
|
Sign up to set email alerts
|

Effective Separation of Human Milk Glycosides using Carbon Dioxide Supercritical Fluid Chromatography

Abstract: Carbohydrate purification remains problematic due to the intrinsic diversity of structural isomers present in nature. Although liquid chromatography‐based techniques are suitable for analyzing or preparing most glycan structures acquired either from natural sources or through chemical or enzymatic synthesis, the separation of regioisomers or linkage isomers with a clear resolution remains challenging. Herein, a carbon dioxide supercritical fluid chromatography (SFC) method was devised to resolve 18 human milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Treatment of 4b with Bf13FT catalysis resulted in two monofucosylated isomers, LNFP III (59%) and LNnFP V (11%), and unreacted LNnT (29%), as displayed in Table (entry 2). The incubation of 4c with Bf13FT produced two monofucosylated isomers, LNFP III (63%) and LNnFP V (11%), and one difucosylated product, LNDFH III (12%), with 14% of LNnT unreacted (Table , entry 3), as determined by supercritical fluid chromatography . These data indicated that the inherent substrate promiscuity of Bf13FT, which led to the synthesis of several fucosylated isomers from LNnT, could be altered by switching the O -azidohexyl linker to the SF 17 tag.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Treatment of 4b with Bf13FT catalysis resulted in two monofucosylated isomers, LNFP III (59%) and LNnFP V (11%), and unreacted LNnT (29%), as displayed in Table (entry 2). The incubation of 4c with Bf13FT produced two monofucosylated isomers, LNFP III (63%) and LNnFP V (11%), and one difucosylated product, LNDFH III (12%), with 14% of LNnT unreacted (Table , entry 3), as determined by supercritical fluid chromatography . These data indicated that the inherent substrate promiscuity of Bf13FT, which led to the synthesis of several fucosylated isomers from LNnT, could be altered by switching the O -azidohexyl linker to the SF 17 tag.…”
Section: Resultsmentioning
confidence: 93%
“…The incubation of 4c with Bf13FT produced two monofucosylated isomers, LNFP III (63%) and LNnFP V (11%), and one difucosylated product, LNDFH III (12%), with 14% of LNnT unreacted (Table 1, entry 3), as determined by supercritical fluid chromatography. 73 These data indicated that the inherent substrate promiscuity of Bf13FT, which led to the synthesis of several fucosylated isomers from LNnT, could be altered by switching the Oazidohexyl linker to the SF 17 tag. This process increased its substrate specificity ( modification of the anomeric position with a short N-methyl oxyamine linker exhibited no effect on catalytic activity and selectivity enhancement.…”
Section: ■ Results and Discussionmentioning
confidence: 95%